The spanish political slogan in the campaign for 2008 general elections - Peña Jiménez, Palma; Ortiz Sobrino, Miguel Ángel (Estudios sobre el Mensaje Periodístico, 2012)
The slogan is a phrase that synthesises the strategy of an electoral campaign: it’s a sharp message that shows the most relevant values of a candidate or a political party. It also grasps the audience attention and summarises the promised benefits. Political parties, as commercial enterprises, do always use a motto that identifies the organisation and its leader, a message repeated in every public event, in every sign, in every outdoor, in every television spot. This article studies the Spanish political slogan, with special attention to the innovations of the last call for general elections.